Inspiratory muscle warm-up and perceptual, physiological, and performance outcomes during exercise in normoxia and hypoxia - Gabler, M. C.; Martin, B. J.; Johnson, B. D.; Schlader, Z. J.; Chapman, R. F. (International Journal of Sports Physiology and Performance, 2025)
Introduction: Some evidence shows that an inspiratory muscle warm-up (IMW) could enhance exercise performance; however, outcomes are mixed, and the mechanistic basis is unclear. Therefore, our purpose was to examine how IMW affects the sensory and affective components of dyspnea, exercise performance, and locomotor muscle oxygenation.